The economics of welfare - Pigou, A. C.; Aslanbeigui, Nahid; Oakes, Guy. (London : Macmillan ; New York : St. Martin's Press, 1960)
The Economics of Welfare provided a solution to the much discussed problem of externalities associated with market inefficiencies such as the problem of pollution. The concept of externalities remains central to modern day welfare economics and particularly environmental economics.
This reissued classic includes a new introduction by Nahid Aslanbeigui and Guy Oakes -- Back cover.
Includes bibliographical references and index.
rpm 03/04/2018
Loans
Keywords: Welfare economics; Finance; Wealth; Economics